Information management and technology strategy in healthcare: local timescales and national requirements - Les Smith; Hugh Preston (Information Research: An International Electronic Journal)
The UK National Health Services strategic switch-back is well documented and each centrally originated change results in various attempts to record the repercussions and predict the outcomes. The most recent shift is embodied in the Department of Healths information strategy, Information for health published in September 1998. This document provides the context for an examination of the issue of developing an Information Management and Technology (IM&T) strategy at the local level within the changing national requirements for NHS information management. The particular pressures on an individual unit and the need to react to them alongside the requirements of the national strategy are the subjects of this article. The case detailed is that of Clatterbridge Centre for Oncology (CCO) on Merseyside, the second largest centre of its type in the UK. Its initial investigation of information needs preceded the publication of the national strategy and its implementation straddled the timescale devised by the NHS Information Authority. The inevitable incompatibility between timescales for the local and the national developments is examined within the case. The work of the new NHS Information Authority and its supporting guidance in its Circular, Information for Health: Initial Local Implementation Strategies, is evaluated as a tool in aligning local and national strategy. Information Managers in other centrally governed organisations within the public sector and large corporations are often alert to similar issues.